“SIX SIGMA” STANDARD AS A LEVEL OF QUALITY OF BIOCHEMICAL LABORATORIES - Pasic, Aleksandra; Sehercehajic, Emir (Sanamed, 2022)
The principal role of biochemical laboratories is responsibility for reliable, reproducible, accurate, timely, and accurately interpreted analysis results that help in making clinical decisions, while ensuring the desired clinical outcomes. To achieve this goal, the laboratory should introduce and maintain quality control in all phases of work. The importance of applying the Six Sigma quality model has been analyzed in a large number of scientific studies. The purpose of this review is to highlight the importance of using six sigma metrics in biochemical laboratories and the current application of six sigma metrics in all laboratory work procedures. It has been shown that the six sigma model can be very useful in improving all phases of laboratory work, as well as that a detailed assessment of all procedures of the phases of work and improvement of the laboratory’s quality control system is crucial for the laboratory to have the highest level of six sigma. Clinical laboratories should use Sigma metrics to monitor their performance, as it makes it easier to identify gaps in their performance, thereby improving their efficiency and patient safety. Medical laboratory quality managers should provide a systematic methodology for analyzing and correcting quality assurance systems to achieve Six Sigma quality-level standards.